Family social environment in childhood and self-rated health in young adulthood - Roustit Christelle; Campoy Eric; Renahy Emilie; King Gary; Parizot Isabelle; Chauvin Pierre (BMC, 2011)
Abstract Background Family social support, as a form of social capital, contributes to social health disparities at different age of life. In a life-course epidemiological perspective, the aims of our study were to examine the association between self-reported family social environment during childhood and self-reported health in young adulthood and to assess the role of family functioning during childhood as a potential mediating factor in explaining the association between family breakup in childhood and self-reported health in young adulthood. Methods We analyzed data from the first wave of the Health, Inequalities and Social Ruptures Survey (SIRS), a longitudinal health and socio-epidemiological survey of a random sample of 3000 households initiated in the Paris metropolitan area in 2005. Sample-weighted logistic regression analyses were performed to determine the association between the quality of family social environment in childhood and self-rated health (overall health, physical health and psychological well-being) in young adults (n = 1006). We used structural equation model to explore the mediating role of the quality of family functioning in childhood in the association between family breakup in childhood and self-rated health in young adulthood. Results The multivariate results support an association between a negative family social environment in childhood and poor self-perceived health in adulthood. The association found between parental separation or divorce in childhood and poor self-perceived health in adulthood was mediated by parent-child relationships and by having witnessed interparental violence during childhood. Conclusion These results argue for interventions that enhance family cohesion, particularly after family disruptions during childhood, to promote health in young adulthood.